SOSIALISASI DAN PELATIHAN PEMBUATAN PERMEN TING-TING JAHE DI DESA KALIBOTO LOR SEBAGAI INOVASI PRODUK UMKM - R, Nadia Putri; Fitriastuti, Viska; Shodik, M Bahrush; Sutikno, Sutikno (JIWAKERTA: Jurnal Ilmiah Wawasan Kuliah Kerja Nyata, 2024)
This study focuses on the socialization and training for producing Ting Ting Ginger Candy in Kaliboto Lor Village, Lumajang Regency. Known for its potential in the micro, small, and medium enterprises (MSME) sector, Kaliboto Lor predominantly produces tempeh and banana chips. However, the product diversity remains limited. Through interviews, it was discovered that ginger is widely grown in the village but underutilized. This training introduces an innovative method to convert ginger into a more practical form—ginger candy—thereby providing a new MSME product. The initiative aims to enhance product variety, competitiveness, and open new business opportunities for the villagers. The study also discusses the health benefits of ginger candy and explores the market potential, considering the large consumer base in Indonesia.